2021
DOI: 10.25034/ijcua.2021.v5n1-6
|View full text |Cite
|
Sign up to set email alerts
|

Urban Land-use and Traffic Congestion: Mapping the Interaction

Abstract: The interaction between transport, land-uses and travel patterns produce diverse transportation problems in urban cities with traffic congestion as the most visible manifestation. Traffic congestion is a frequent phenomenon in most cities around the globe. This paper reviews the interaction between land-use traffic congestion through published literature. The objective of this study is to encourage and provide researchers with future research directions in land-use and traffic congestion. For this purpose, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There is a causal connection between unsustainable urban growth and the problem of accessibility in Lagos due to the leading role of the city as national economic and industrial hub. Also, post-colonial Land Use Act 1978) minimized government authority and lent local lease holders, private individuals and informal players unhinged power of influence, the variables that resulted in weak land management, sub-optimal development planning, and mosaics of urban sprawls and slums with persistent mobility issues (Oluwatayo et al, 2019;Kanyepe et al, 2021).…”
Section: Classified Lulc Imageriesmentioning
confidence: 99%
“…There is a causal connection between unsustainable urban growth and the problem of accessibility in Lagos due to the leading role of the city as national economic and industrial hub. Also, post-colonial Land Use Act 1978) minimized government authority and lent local lease holders, private individuals and informal players unhinged power of influence, the variables that resulted in weak land management, sub-optimal development planning, and mosaics of urban sprawls and slums with persistent mobility issues (Oluwatayo et al, 2019;Kanyepe et al, 2021).…”
Section: Classified Lulc Imageriesmentioning
confidence: 99%
“…Several studies have analyzed poverty and poor fairness in the distribution of national income, given the importance of analyzing that phenomenon and its reflection on society. A study prepared by [5] and the researcher Muhammad Hassan Odeh analyzed welfare and its relationship to average and fair national income. It concluded that there are economic and social distortions in the Iraqi economy, which prompted the government to adopt a policy of support and intervention, which carried a great burden on the public budget to achieve and reach the economic well-being of citizens [6].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition to having an impact on changes in land use, the construction of the Exit Toll also has an impact on increasing the volume of vehicles on the Jalan Otto Iskandardinata corridor. The high level of land use is directly proportional to the movement of the traffic flow it produces (Kanyepe et al, 2021;Surya et al, 2020). However, the findings from the field show that the Jalan Otto Iskandardinata corridor does not yet have a good-quality infrastructure.…”
Section: Introductionmentioning
confidence: 97%